2012
DOI: 10.1007/s00122-011-1769-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of fruit quality traits in the octoploid cultivated strawberry highlights the role of homoeo-QTL in their control

Abstract: Fruit quality traits are major breeding targets in the Rosaceae. Several of the major Rosaceae species are current or ancient polyploids. To dissect the inheritance of fruit quality traits in polyploid fleshy fruit species, we used a cultivated strawberry segregating population comprising a 213 full-sibling F1 progeny from a cross between the variety ‘Capitola’ and the genotype ‘CF1116’. We previously developed the most comprehensive strawberry linkage map, which displays seven homoeology groups (HG), includin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
153
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(170 citation statements)
references
References 109 publications
(161 reference statements)
15
153
2
Order By: Relevance
“…An orthologous QTL is a viable hypothesis because a recent study of the cultivated hybrid strawberry (F. Â ananassa subsp. ananassa) concluded that B25% of QTL for fruit traits were at orthologous positions on a different homoeologous LGs, that is, were putative 'homoeo-QTL' (Lerceteau-Köhler et al, 2012), and these may be segregating in the natural hybrid species as well. Moreover, there is no evidence for transposition of other markers, which might be expected if nonhomologous recombination triggered the QTL at this position.…”
Section: Discussionmentioning
confidence: 99%
“…An orthologous QTL is a viable hypothesis because a recent study of the cultivated hybrid strawberry (F. Â ananassa subsp. ananassa) concluded that B25% of QTL for fruit traits were at orthologous positions on a different homoeologous LGs, that is, were putative 'homoeo-QTL' (Lerceteau-Köhler et al, 2012), and these may be segregating in the natural hybrid species as well. Moreover, there is no evidence for transposition of other markers, which might be expected if nonhomologous recombination triggered the QTL at this position.…”
Section: Discussionmentioning
confidence: 99%
“…When the probability was lower than 0.05, co-localization of QTL was considered to have occurred by a genetic process rather than by chance (Lerceteau-Köhler et al 2012).…”
Section: Remobilizationmentioning
confidence: 99%
“…While certain traits in strawberry, particularly disease resistance, are controlled by major genes located to a single subgenome, 19–21 other traits are controlled by alleles across multiple subgenomes. 22 In the University of Florida strawberry breeding program, which develops cultivars for annualized winter and early-spring production systems, the genetic architectures of several complex yield and fruit quality traits 23 have been described, for which no significant QTL or only a few minor-effect QTLs have been detected. 18 …”
Section: Introductionmentioning
confidence: 99%